2021
DOI: 10.1186/s12889-021-10762-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with sexually transmitted infections among care-seeking adults in the African Cohort Study

Abstract: Objectives Sexually transmitted infections (STIs) are a major cause of morbidity. Understanding drivers of transmission can inform effective prevention programs. We describe STI prevalence and identify factors associated with STIs in four African countries. Methods The African Cohort Study is an ongoing, prospective cohort in Kenya, Nigeria, Tanzania and Uganda. At enrollment, a physical exam was conducted and STI diagnosis made by a clinician usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…7 Younger age, lower education level, and unmarried as opposed to married relationship status have all been shown to be associated with increased STI risk in other studies. 6,9,17,21 Further, in our study, 41% of women in the testing arm were enrolled at Old Naledi Clinic which is located in a neighbourhood with poorer socioeconomic conditions, compared to the other recruitment sites. Although we could not compare income level with the previous studies conducted in Botswana, due to lack of income data reported, these social and economic factors could explain the higher STI prevalence observed in our study.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…7 Younger age, lower education level, and unmarried as opposed to married relationship status have all been shown to be associated with increased STI risk in other studies. 6,9,17,21 Further, in our study, 41% of women in the testing arm were enrolled at Old Naledi Clinic which is located in a neighbourhood with poorer socioeconomic conditions, compared to the other recruitment sites. Although we could not compare income level with the previous studies conducted in Botswana, due to lack of income data reported, these social and economic factors could explain the higher STI prevalence observed in our study.…”
Section: Discussionmentioning
confidence: 77%
“…7 Younger age, lower education level, and unmarried as opposed to married relationship status have all been shown to be associated with increased STI risk in other studies. 6,9,17,21 Further, in our study, 41% of women in the testing arm were enrolled at Old Naledi Clinic which is located in a neighbourhood with poorer socioeconomic conditions, compared to the other recruitment sites.…”
Section: Discussionmentioning
confidence: 88%
“…All AFRICOS participants received the standard of care associated with their PEPFAR-supported site. The details of this study, as well as the characteristics of each study site, have also been previously described 20 , 21 . The NHS has been approved centrally by the Uniformed Services University (USU) Institutional Review Board (IRB) and at each participating site.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies showed that health care-seeking behavior is affected or influenced by different factors like lack of money, distance from the health facility, age, educational status, residence, occupation, age at first sex, number of sexual partners, use of a condom, being tested for HIV, media exposure, wealth index cultural beliefs and practices are some of the identified factors which affect the health care seeking behavior of women [ 13 18 ].…”
Section: Introductionmentioning
confidence: 99%